(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Purpose – In this research work, emphasis is made on collecting society response and acceptance levels of technologies developed and transferred by TVET Institutions. Critical information on the technical and performance parameters of transferred technologies was received from many respondents who were closely associated with society. Design/methodology/approach – The methodology included questionnaires based on 5-point Likert scale questionnaire with an objective to ascertain the acceptance levels of technologies developed and transferred by TVET Institutions. The questionnaire contained queries addressing variety of issues, like type of technologies developed and developing, manpower participating in technology development, problems associated with technology development and transfer. The methodology followed was based on the analysis of the response received on technical questionnaire that was designed and responses received from the people located in Addis Ababa city Practical Implications: COVID-19 has been rising and mutating in many countries since it was discovered by the end of 2019. Many countries, including Ethiopia has seen the spike and fall of COVID-19 regularly. This non-linear behavior of COVID-19 infection rate curves around the world has prompted many educational institutions like TVET (Technical Vocational and Education Training) institutions located in Addis Ababa to develop and transfer technologies like hand washing machines, face masks, sanitizers and other anti-covid technologies. These equipment’s posse’s characteristic simple operational and quality properties like usability, functionality, efficiency, etc. This research will help to gather the technical information pertaining to design, quality and performance of Hand washing equipment’s, face masks, Hand sanitizers and other equipment’s from the society. Findings - Divergent and constructive opinions were received from the society to improve and meet the ever-rising demand for anti-COVID-19 technologies. The user response on developed and transferred technology prove the usefulness to combat COVID-19 spread but also finds many applications with in the life of the public. Cronbach alpha reliability test value of 0.73 was obtained after analysis of the response data. The results prove the excellence and consistency of the responses received on the development and transferred technologies. Overall, the research findings help to build and transfer most robust, quality and cost-effective technologies that is a need of the hour to fight against COVID-19 transmission. Originality/value – COVID-19 has posed many challenges to public and has resulted in many deaths in Addis Ababa and entire Ethiopia. This work is unique and would make valuable contribution and gather information from the society on the design and technical aspects of developed and transferred technologies by TVET Institutions used for combating COVID-19.